Prescription Pattern of Antihypertensive Drugs in Chronic Kidney Disease Patients Attending - A Tertiary Care Hospital (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Chronic kidney disease exists both as a common cause of hypertension and complication of uncontrolled hypertension. This complex interplay of hypertension and CKD further increases the risk of adverse cardiovascular and cerebrovascular outcomes. Blood pressure control is pertinent in all stages of chronic kidney disease.Method: An observational descriptive cross-sectional study was conducted in Nephrology Department of Dhaka Medical College Hospital from January 2022 to December 2022.  Total 264 hypertensive CKD patients were included in this study according to selection criteria. Collected data were processed and analyzed by using SPSS 26.0. p value of < 0.05 was taken as statistically significant.Result: Among 264 CKD patients 58% male, 42% female and mean age was 49.43±13.87years. Only 67% patient achieved control of BP with antihypertensive. 53.8% patient were in stage-5 and 18.2% in stage-4 CKD. 85.6% patient received combination therapy. Among them 58.3% patients received two drug combination therapy. CCBs was prescribed in 169 patients. Amlodipine was 41.42% the preferred CCB and the combination of ARBs+CCBs was (28.7%) the frequently prescribed. Control of blood pressure was achieved in CKD patients taking monotherapy (p = 0.039) and on three drug combination therapy (p = 0.006).Conclusion: Calcium channel blocker is the treatment of choice in CKD patients with hypertension and commonly prescribed CCB is amlodipine. Combination of antihypertensive therapy is a better choice for control of hypertension.J Com Med Col Teachers Asso July 2024; 28(2): 70-74